Chemical vapor deposition growth of tin oxide nanowires for electrochemical sensor development. (6th November 2022) - Hai, Nguyen Hoang; Nguyen, Minh Hieu; Tuan, Mai Anh
Abstract: This paper reports a growth of tin oxide nanowires on gold patterns by chemical vapor deposition. A 90 nm gold layer was deposited on a silicon wafer using a sputtering system and pre‐pattern by lift‐off techniques. Tin oxide nanowires were selectively grown on the gold pattern by chemical vapor deposition technique with 750°C and 5 × 10 ‐2 torr. High resolution transmission electron microscopy measurements showed that nanowire possessed a single crystal nature with tetragonal crystal system and the calculated lattice constants (a = 0.474 nm; c = 0.318 nm) were closed to those of standard pattern of SnO2 . The ready SnO2 nanowire grown on the gold patterns were investigated for electrochemical sensor development. Abstract :